A binder-free electrode architecture design for lithium–sulfur batteries: a review. Issue 6 (20th May 2019) - Guo, Junling; Liu, Jinping
Abstract : Binder-free structures offering structural and kinetic advantages for constructing high performance sulfur cathodes and dendrite-free Li metal anodes are reviewed. Abstract : Lithium–sulfur batteries (LSBs) are considered to be one of the most promising next-generation electrochemical power sources to replace commercial lithium-ion batteries because of their high energy density. However, practical application of LSBs is hindered by two critical drawbacks: "redox shuttle reactions" of dissolved polysulfides at the cathode side and Li dendrites at the Li anode side. Therefore, various approaches have been proposed to break down technical barriers in LSB systems. The overall device performance of LSBs depends on not only the development of host materials but also the superior architecture design of electrodes. Among these architectures, binder-free electrodes are verified to be one of the most effective structural designs for high-performance LSBs. Therefore, it is urgent to review recent advances in binder-free electrodes for promoting the fundamental and technical advancements of LSBs. Herein, recently emergent studies using various binder-free architectures in sulfur cathodes and lithium metal anodes are reviewed. These binder-free electrodes, with well-interconnected structures and abundant structural space, can provide a continuous pathway for fast/uniform electron transport/distribution, load sufficient active materials for ensuring high energy density, and afford large electrochemically active surface areas where electrons and Li ions can come into contact with the active materials for fast conversion reactions, thus leading to suitable applications for LSBs. Subsequently, the advantages and challenges of binder-free architectures are discussed from several recently emergent studies using binder-free structured sulfur cathodes or Li metal anodes. The future prospects of LSBs with binder-free electrode structure designs are also discussed.